The effect of maternal pregestational diabetes on fetal autonomic nervous system - Luis Mercado; Diana Escalona‐Vargas; Sarah Blossom; Eric R. Siegel; Julie R. Whittington; Hubert Preissl; Kaitlyn Walden; Hari Eswaran (Physiological Reports, 2023)
Abstract Heart rate variability assessment of neonates of pregestational diabetic mothers have shown alterations in the autonomic nervous system (ANS). The objective was to study the effect of maternal pregestational diabetes on ANS at the fetal stage by combining cardiac and movement parameters using a non‐invasive fetal magnetocardiography (fMCG) technique. This is an observational study with 40 participants where fetuses from a group of 9 Type 1, 19 Type 2 diabetic, and 12 non‐diabetic pregnant women were included. Time and frequency domain fetal heart rate variability (fHRV) and coupling of movement and heart rate acceleration parameters related to fetal ANS were analyzed. Group differences were investigated using analysis of covariance to adjust for gestational age (GA). When compared to non‐diabetics, the Type 1 diabetics had a 65% increase in average ratio of very low‐frequency (VLF) to low‐frequency (LF) bands and 63% average decrease in coupling index after adjusting for GA. Comparing Type 2 diabetics to non‐diabetics, there was an average decrease in the VLF (50%) and LF bands (63%). Diabetics with poor glycemic control had a higher average VLF/LF (49%) than diabetics with good glycemic control. No significant changes at p < 0.05 were observed in high‐frequency (HF) frequency domain parameters or their ratios, or in the time domain. Fetuses of pregestational diabetic mothers exhibited some differences in fHRV frequency domain and heart rate‐movement coupling when compared to non‐diabetics but the effect of fHRV related to fetal ANS and sympathovagal balance were not as conclusive as observed in the neonates of pregestational diabetic mothers.